Expanding the Role of the Perioperative Educator - Panneton, Yves (Operating Room Nurses Association of Canada Journal, 2000)
Perioperative educators mostly conduct orientation, in service and continuing education to perioperative staff. Their role can be expanded to improve the quality and efficiency of perioperative care. To this end, an organizational communication model can be used to identify weaknesses and guide intervention. To be effective with this approach, perioperative educators have to work closely with perioperative managers.